The Malays civilization from Southeast Asia Maritime realm perspectives / Rohani Mohd Shah ... [et al.] - Mohd Shah, Rohani; Husin, Zaliha; Abd Rahman, Hamisah; Haris, Balqis (2015)
Since the turn of the first millennium C.E, Southeast Asian sailors have been important actors in world history. Long before the Portuguese arrived in Asian waters, sailors from East Africa to East Asia had already been drawn to Southeast Asian port. Indeed, we will reveal some of the less obvious interest of the information on Malays lifestyles that do not receive much attention in the power's history records, nor from scholars who study them in the present. The origins of the Malays, the influence of Malays sailor in the early navigation world, Malays skill as metallurgists and the technical acknowledged in creating navigations tools has led the Indian literature in B.C. E to praise the Malays sailor as the speedy sailor. The Malays peninsula as the Land of Gold and welcomed by the Greek in ten century ahead of the Chinese for want of the variety of spices and cinnamon. Even the Arab's text in thirteen century, acknowledged Malay sailors, playing a leading role in navigation and in fifteen centuries the Portuguese soldiers addressed the Malays town as the Venice of the East. We conclude the paper by establishing the history that it is the Malays sailor ability to ride the wave faster than others at sea, the lifestyle that gives a true meaning of one society reflected in the words "Tanah-air".